Fatting the brain: a brief of recent research - Hussain, Ghulam; Schmitt, Florent; Loeffler, Jean-Philippe; Gonzalez De Aguilar, Jose L. (Frontiers in Cellular Neuroscience, 2013)
Fatty acids are of paramount importance to all cells, since they provide energy, function as signaling molecules, and sustain structural integrity of cellular membranes. In the nervous system, where fatty acids are found in huge amounts, they participate in its development and maintenance throughout life. Growing evidence strongly indicates that fatty acids in their own right are also implicated in pathological conditions, including neurodegenerative diseases, mental disorders, stroke and trauma. In this review, we focus on recent studies that demonstrate the relationships between fatty acids and function and dysfunction of the nervous system. Fatty acids stimulate gene expression and neuronal activity, boost synaptogenesis and neurogenesis, and prevent neuroinflammation and apoptosis. By doing so, they promote brain development, ameliorate cognitive functions, serve as anti-depressants and anti-convulsants, bestow protection against traumatic insults and enhance repairing processes. On the other hand, unbalance between different fatty acid families or excess of some of them generate deleterious side effects, which limit the translatability of successful results in experimental settings into effective therapeutic strategies for humans. Despite these constraints, there exists realistic evidence to consider that nutritional therapies based on fatty acids can be of benefit to several currently incurable nervous system diseases.